Water-in-Oil-in-Water (W/O/W) Double Emulsion Morphology and Its Degradation on Instant Noodle Seasoning - Irene Raras Nawangsasi; Yoyok Budi Pramono; Antonius Hintono; Vita Paramita (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
This experiment aims to the observed morphology, reduction of fineness and distribution particle deterioration of W/O/W double emulsion in instant noodle seasonings which is kept in 3 weeks with different storage temperature and NaCl level treatments. Emulsion structure has an important role to hamper salt release rate from internal to external phase. Structure breakdown shows system inability to maintain continuous salty taste perception during consumption because of the increasing salt release rate in storage period of instant noodle seasoning. Samples are treated with 3 variations of storage temperatures which are low (4 °C), room (25 °C), high temperature (40 °C) and 6 variations of NaCl level which are 0; 0,2; 0,4; 0,6; 0,8; 1%. Samples are categorized into 2 groups, double emulsions, and instant noodle seasonings. The double emulsion is made by 2 phases emulsification to get primary W/O emulsion and final W/O/W emulsion. This experiment showed that low and high-temperature storage affected emulsion and seasoning particle morphology, fineness and distribution throughout several instability phenomena.